Day 1 Mon, May 01, 2017 2017
DOI: 10.4043/27609-ms
|View full text |Cite
|
Sign up to set email alerts
|

Nano-Enhanced Elastomers for Oilfield Applications

Abstract: The use of elastomers in oil industry extends over a broad range of applications including seals, packing elements, reactive rubber elements, stators, and pads. These applications require a variety of property requirements that may differ for dynamic and static applications or include a need for stimuli-responsive capabilities in certain tools. This research details the effect of nanofillers on elastomer properties for oil and gas components. The effects include enhancement of mechanical propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…As the result, it was found that CNTs enable a superior wear resistance. 15,16 The HNBR reinforcement with as little as 15 phr of CNTs provided better resistance to wear than 50 phr of N234 carbon black. The difference in performance was even more drastic when compared with 50 phr of generalpurpose carbon black grades N550 and N326 (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As the result, it was found that CNTs enable a superior wear resistance. 15,16 The HNBR reinforcement with as little as 15 phr of CNTs provided better resistance to wear than 50 phr of N234 carbon black. The difference in performance was even more drastic when compared with 50 phr of generalpurpose carbon black grades N550 and N326 (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Polymer chains of HNBR and XHNBR were cross-linked through reactions with peroxide, whereas carboxyl groups of XHNBR and functionalized CNTs were cross-linked by metal ions, e.g., Zn 2+ or Zr 4+ originating from zinc oxide and zirconium(IV) tert-butoxide, respectively, added to the mix. 19,20 The proposed schematics of the cross-linking reaction mechanism ultimately leading to the formation of hybrid elastomer nanocomposites suitable for high-temperature applications are shown on Figure 5.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Colloidal systems of functionalized nanoparticles have been evaluated in oil industry for enhanced oil recovery, formation damage remediation, flow assurance, and water treatment operations [1]- [8]. Surface modified nanoparticles have also been considered for applications as tracers in reservoir studies, active media in thermal management fluids, and fillers in high performance elastomers [9] [10] [11] [12] [13]. Conventional functionalization of nanoparticles, which mostly use alkoxysilanes and chlorosilanes for covalent bonding to surface, need catalytic amount of water for the reactions to proceed, require multiple hours to fully saturate the surface, and release by-products capable of interfering with the desired functional or chemical behavior of the modified surface [14].…”
Section: Introductionmentioning
confidence: 99%